If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7t = t + 54 Reorder the terms: 7t = 54 + t Solving 7t = 54 + t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1t' to each side of the equation. 7t + -1t = 54 + t + -1t Combine like terms: 7t + -1t = 6t 6t = 54 + t + -1t Combine like terms: t + -1t = 0 6t = 54 + 0 6t = 54 Divide each side by '6'. t = 9 Simplifying t = 9
| x^2+6x+8=3(y^2)+6y+2 | | 4t=t+57 | | 3a=a+18 | | 2y=y+16 | | 5c=c+56 | | (2x+1)(2x+3)=0 | | u+39=4u | | 3x/5-5x/2 | | x+2y-3z=3 | | 4(x-3)+7=2x | | 2q=q+26 | | 12-0.4t=0 | | 3z=z+48 | | w^2+4=0 | | sin(6x)=3sin(2x) | | 3m^2-5m-372=0 | | 7x^3-10x^2-25x+200=0 | | 9/3*2 | | 9/3x2 | | (Z+5)(z-3)=0 | | 9/3y | | (3x+12)-(2x-4)=0 | | (W+12)(w-2)=0 | | 2x+3x+1=16 | | 2(4)+3(2)(-4)-4(16)= | | y=-8+-1t+-2x+0.5x^2 | | y=0.5x^2+2x-8-4x-t | | 2(x+3)-7=9 | | (4x-5)/4-(2x-1)/6=x | | (2x-4)+(6-x)=0 | | 3(x-1)-4(2x+3)=5 | | (3-x)/6=x/3 |